Estimation of efficiency of comprehensive dental rehabilitation of patients with separate oral cavity precautions - I. N. Khalyavina; O. S. Gileva; T. V. Libik; S. V. Koshkin; E. A. Kuklina; N. S. Kuklin (LLC "Endo Press", 2020)
Relevance. The prevalence of precancerous diseases in the structure of the pathology of the oral mucosa in patients of the Russian Federation is quite high (up to 35%) and has no tendency to decrease, which actualizes the search for more effective methods of complex treatment and rehabilitation to improve the patient's quality of life and prevention of malignancy.Aim. To present a comparative assessment of the effectiveness of conservative surgical dental treatment in combination with restorative rehabilitation of patients with oral lichen planus.Materials and methods. The study assessed the effectiveness of complex conservative surgical treatment and prosthodontic rehabilitation of patients with the most frequently detected form of oral precancer lichen planus.Results. Based on a comprehensive assessment of objective and subjective indicators, the feasibility and advantages of an integrated approach to the treatment and rehabilitation of patients with lichen planus are substantiated, including the local use of highly active topical steroids / calcineurin inhibitors, electrocoagulation of hyperkeratosis sites until stable remission with subsequent prosthetic treatment using biocompatible materials, rational designs, atraumatic techniques, including implant dental prosthetics.Conclusion. Conducting a rational prosthodontic rehabilitation upon completion of the conservative-surgical treatment stage provided a 6.5-month longer remission of the disease compared with the control group.